The Influence of Airline Service Quality, Punctuality of Flight Times, and Brand Image on Passenger Loyalty at Soekarno Hatta Airport - Achmad, Achmad; Simarmata, Juliater; Candra Susanto, Primadi (Dinasti Publisher, 2024)
The article on the influence of airline service quality, flight punctuality and brand image on passenger loyalty at Soekarno Hatta Airport is a scientific literature article within the scope of marketing management science. The purpose of this writing is to build a hypothesis regarding the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and the journal Sinta. The results of this article are: 1) Airline service quality influences passenger loyalty at Soekarno Hatta Airport; 2) Punctuality of flight times influences passenger loyalty at Soekarno Hatta Airport; and 3) Brand image influences passenger loyalty at Soekarno Hatta Airport.